PERSEPSI PENGUNJUNG PADA ATRAKSI WISATA PULAU CINTA TELUK JERING KABUPATEN KAMPAR PROVINSI RIAU - Dinesti Sastri; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Tourist attraction is something that becomes an attraction and can impress tourists in the form of satisfaction, comfort, and pleasure to tourists who see it or do it. In this case, it can be in the form of natural, cultural, and man-made attractions. This study aims to determine the tourist attraction of Cinta Island in Kampar Regency, Riau Province and to determine the visitor's perception of the Cinta Island tourist attraction in Kampar Regency, Riau Province. In this study, the author uses quantitative methods as a procedure for processing data, while the data collection techniques used are observation, questionnaires and documentation using a Likert scale as a measuring tool. Based on the results of the study, Tourism Attractions on Cinta Island Teluk Jering, Kampar Regency, Riau Province, with research conclusions in the good category. Keyword : perceptions, visitors, tourist attractions.